Gender and racial inequalities in trends of oral cancer mortality in Sao Paulo, Brazil - Jose Leopoldo Ferreira Antunes (Revista de Saúde Pública, 2013)
OBJECTIVE: To analyse recent trends in oral cancer mortality, focusing specifically on differences concerning gender and race. METHODS: Official information on deaths and population in the city of Sao Paulo, 2003 to 2009, were used to estimate mortality rates from oral cancer (C00 to C10, International Classification of Diseases, 10th Revision), adjusted for age and stratified by gender (females and males) and race (blacks and whites). The Prais-Winsten auto-regression procedure was used to analyse the time series. RESULTS: During the study period, 8,505 individuals living in the city of Sao Paulo died of oral cancer. Rates increased for females (rate of yearly increase = 4.4%, 95%CI 1.4;7.5), and levelled off for men, which represents an inversion of previous trends among genders in the city. Increases were identified for blacks, with a high rate of yearly increase of 9.1% (95%CI 5.5;12.9), and levelled off for whites. Oral cancer mortality in blacks almost doubled during the study period, and surpassed mortality in whites for almost all categories. CONCLUSIONS: Mortality presented a higher increase among women than in men, and it doubled among backs. The surveillance of trends of oral cancer mortality across gender and racial groups may contribute to implementing socially appropriate health policies, which concurrently reduce the burden of disease and the attenuation of unfair, avoidable and unnecessary inequalities in health.